Human blood liquid memristor. (1st January 2011) - Kosta, S.P.; Kosta, Y.P.; Bhatele, Mukta; Dubey, Y.M.; Gaur, Avinash; Kosta, Shakti; Gupta, Jyoti; Patel, Amit; Patel, Bhavin
An experimental study on a physical model of memristor made from human blood (as material of resistor) is presented. The model manifests memristor characteristics as defined by Professor Leon Chua (1971), Strukov (2008) and William (2008). Speculative potential applications in human healthcare science and electronic memory circuit science/technology is envisaged.